Identification of Community Knowledge on Lead Contamination and Analysis of Lead Level in Fish - Nurwulan, Sita; Damayanti, Sophi; Amalia, Lia (UI Scholars Hub, 2022)
Poisoning is an event of human exposure to poisonous substances that are harmful to the body at certain doses. Lead is a heavy metal that can cause toxicity, including neurotoxic effects, hypertension, digestive system disorders, bone and tooth growth disorders, immune system disorders, infertility, and fetal disorders. Fish is a source of nutrients that are often consumed by people, however can also accumulate lead. This study aimed to analyze the lead level in fish and identify the community knowledge level regarding lead contamination in fish. Identification of community knowledge levels regarding lead. Identification of community knowledge levels regarding lead contamination in fish was conducted on three hundred respondents consisting of School of Pharmacy (SF) Institut Teknologi Bandung (ITB) one hundred students, one hundred community, and one hundred housewives. This study also analyzed lead levels in six fish samples using Graphite Furnace Atomic Absorption Spectroscopy (GFAAS). As the result, SF ITB students had the highest level of knowledge in the definition of lead (97%), lead poisoning (98%), fish lead accumulation (75%), the poisoning effects of lead, and sources of lead. However, all of the respondents had a low level of knowledge regarding regulations about lead levels in fish. The lead levels analysis on fish showed that three out of six samples had lead levels that exceeded the limit of lead contamination (>0.2 g/kg). The study indicated that respondents’ knowledge regarding lead contamination in fish is still low and lead-contaminated fish is still being sold on the market.